Despicable role of epithelial–mesenchymal transition in breast cancer metastasis: Exhibiting de novo restorative regimens - Paras Famta; Saurabh Shah; Biswajit Dey; Kondasingh Charan Kumar; Deepkumar Bagasariya; Ganesh Vambhurkar; Giriraj Pandey; Anamika Sharma; Dadi A. Srinivasarao; Rahul Kumar; Santosh Kumar Guru; Rajeev Singh Raghuvanshi; et al. (Cancer Pathogenesis and Therapy)
Breast cancer (BC) is the most prevalent cancer in women globally. Anti-cancer advancements have enabled the killing of BC cells through various therapies; however, cancer relapse is still a major limitation and decreases patient survival and quality of life. Epithelial-to-mesenchymal transition (EMT) is responsible for tumor relapse in several cancers. This highly regulated event causes phenotypic, genetic, and epigenetic changes in the tumor microenvironment (TME). This review summarizes the recent advancements regarding EMT using de-differentiation and partial EMT theories. We extensively review the mechanistic pathways, TME components, and various anti-cancer adjuvant and neo-adjuvant therapies responsible for triggering EMT in BC tumors. Information regarding essential clinical studies and trials is also discussed. Furthermore, we also highlight the recent strategies targeting various EMT pathways. This review provides a holistic picture of BC biology, molecular pathways, and recent advances in therapeutic strategies.